2017
DOI: 10.20965/jdr.2017.p0585
|View full text |Cite
|
Sign up to set email alerts
|

Research and Development of a Non-Destructive Inspection Technique with a Compact Neutron Source

Abstract: Neutrons have the power to penetrate metals or heavy elements such as calcium, silicon, and iron. Neutrons also have high sensitivity, so they can be used to detect elements such as boron and chlorine. An accelerator-driven, compact neutron system has been developed in RIKEN for practical use on job sites.In this paper, a pixel imaging detector for fast neutrons with energy levels above 1 MeV is developed and used to produce images of an iron rod and air pockets through 30 cm of concrete. Also, the salt concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
2

Relationship

5
5

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…The RIKEN accelerator-driven compact neutron source (RANS) is one of the first compact neutron sources that has been developed especially for practical industrial use in the field of manufacturing and non-destructive inspections on-site [6]. RANS generates pulsed neutrons from a Be (p, n) reaction with 7 MeV and 100 A proton beams.…”
Section: Pulsed Neutron Sourcesmentioning
confidence: 99%
“…The RIKEN accelerator-driven compact neutron source (RANS) is one of the first compact neutron sources that has been developed especially for practical industrial use in the field of manufacturing and non-destructive inspections on-site [6]. RANS generates pulsed neutrons from a Be (p, n) reaction with 7 MeV and 100 A proton beams.…”
Section: Pulsed Neutron Sourcesmentioning
confidence: 99%
“…In the conventional nondestructive inspection method using neutron transmission, the sample should be interposed between a neutron source and a detector (de Beer et al 2004;Justnes et al 1994;Kawabata et al 2004;Otake et al 2017). however, the applicable environment is limited.…”
Section: Compact and Lightweight Design For On-site Applicationsmentioning
confidence: 99%
“…Non-destructive technique without core sampling is desirable to assay many structures. To meet the demand, we have started the development of on-site non-destructive technique for salt distribution in concrete by prompt gamma neutron activation analysis (PGNAA) at the RIKEN acceleratordriven compact neutron source (RANS) [5]. So far, we have experimentally confirmed that RANS provides suitable neutron fluxes to detect small enough amounts of chlorine within the marginal concentration of around 1.2 kg/m 3 to involve steel corrosion, by applying PGNAA to 4x4x4cm 3 mortar bricks of different chloride ion concentrations from 0.36 to 5.1 kg/m 3 [6,7].…”
Section: Introductionmentioning
confidence: 99%